An Optional Instrument for European Insurance Contract Law - Lakhan, Mandeep; Heiss, Helmut (Utrecht Journal of International and European Law, 2010)
The Principles of European Insurance Contract Law, also referred tousing the acronym PEICL, were published in September 2009. They are the result of ten years of academic work undertaken by the"Restatement of European Insurance Contract Law" Project Group. In the time since its establishment in 1999, the project has been transformed from being a stand-alone project to a part of the CoPECL (Common Principles of European Insurance Contract Law) network, drafting a specific part of the Common Frame of Reference. Having continually worked under the guiding principle that "the law of insurance [in Europe] must be one," it now represents a serious option for providing Europe with a single legal framework for insurance contracts.Despite the European Council's proclamations that the Common Frame of Reference will remain a non-binding instrument, the implementation of one or more optional instruments in the future does not appear to beimprobable considering recent developments. The possibility of anoptional instrument has been expressed more than once by the European Commission in its Action Plan and Communication on European Contract Law. Other indications in favour of an optional instrument include the European Parliament's repeated references to the Common Frame of Reference as providing, at the very least, a model for a futureoptional instrument, as well as the EESC's earlier proposal of anoptional instrument as an alternative to standardising insurancecontract law. The preparation by the EESC of another (own-initiative) opinion on European contract law is underway, and its presentation is anticipated in 2010. Hence, the optional instrument is evidently the subject of serious political deliberation. Using Article 1:102, the Principles of European Insurance Contract Law represent a prototype for such an instrument.